2005
DOI: 10.1186/1471-2458-5-103
|View full text |Cite
|
Sign up to set email alerts
|

Work ethics and general work attitudes in adolescents are related to quality of life, sense of coherence and subjective health – a Swedish questionnaire study

Abstract: Background: Working life is an important arena in most people's lives, and the working line concept is important for the development of welfare in a society. For young people, the period before permanent establishment in working life has become longer during the last two decades. Knowledge about attitudes towards work can help us to understand young people's transition to the labour market. Adolescents are the future workforce, so it seems especially important to notice their attitudes towards work, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…No significant differences between the groups were noted in the social or economic dimensions, which is contrary to findings reported by Axelsson et al [ 24 ], who reported that positive attitudes toward occupational life may increase QOL score.…”
Section: Discussioncontrasting
confidence: 99%
“…No significant differences between the groups were noted in the social or economic dimensions, which is contrary to findings reported by Axelsson et al [ 24 ], who reported that positive attitudes toward occupational life may increase QOL score.…”
Section: Discussioncontrasting
confidence: 99%
“…Young people who are out of work report reduced quality of life, and quality of life is linked not only to good health but also to self-esteem, satisfaction with free time and decision latitude. For this reason, effort should aim at empowering unemployed young adults by identifying their concerns and resources [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vocation can strengthen the sense of coherence when expectations are known and consistent, when a worker experiences having the resources required to complete job tasks, and when the worker believes that he/she has a shared responsibility (Lustig, Rosenthal, Strauser, & Haynes, 2000). Sense of coherence is a factor in work-related phenomena such as sick leave processes (Falkdal, Edlund, & Dahlgren, 2006), disability leading to pension (Suominen et al, 2005), work and well-being (Virtanen & Koivisto, 2001), work attitudes (Axelsson, Andersson, Håkansson, & Ejlertsson, 2005), work stressors and strain Kivimäki, Kalimo, & Toppinen, 1998), profession or kind of employment (Lundberg & Nyström Peck, 1994), and quality of work .…”
Section: Introductionmentioning
confidence: 99%